Exploring Treatment Protocol Adherence and Variations in Paroxysmal Supraventricular Tachycardia in the Emergency Department: A Multi-Center Cohort Study - Kevin Ku; Jack Healy; Christian A. Lee; Maha Khan; Kevin D. Chao; Saleh Hassan; Ching-Fang Tiffany Tzeng; Yu-Lin Hsieh; Andrew Shedd; Toral Bhakta; Dahlia Hassani; Eric H. Chou (Medical Sciences, 2025)
Background: Supraventricular tachycardia (SVT) is a common arrhythmia requiring prompt intervention in the emergency department (ED). Despite evidence-based guidelines recommending a stepwise approach, significant variability in clinical practice persists, particularly in adenosine dosing strategies. Objective: This study assessed adherence to SVT treatment protocols in the ED, focusing on the efficacy of an initial 6 mg versus 12 mg adenosine dose and the use of alternative pharmacologic agents. Methods: This multi-center, retrospective cohort study analyzed adult patients (≥18 years) diagnosed with stable SVT in urban EDs across North Texas between 1 January 2019, and 16 January 2022. Patients who spontaneously converted to normal sinus rhythm or presented with hemodynamically unstable SVT requiring immediate cardioversion were excluded. The primary outcome was the rate of successful conversion to sinus rhythm. Secondary outcomes included frequency of adenosine administration, deviations from 2020 AHA ACLS guidelines in SVT treatment, and risk factors associated with failure to convert to sinus rhythm following adenosine administration. Results: A total of 439 patients were included in the final analysis. Vagal maneuvers were attempted in 26% of cases, achieving a 31% success rate. Adenosine was used in 83% of pharmacologic interventions, with 57.5% receiving 6 mg and 42.5% receiving 12 mg as the initial dose. The 12 mg dose had a significantly higher conversion rate (54.2% vs. 40.6%, p = 0.03). Regression analysis identified key predictors of treatment success, including comorbidities, and baseline hemodynamics. Documentation inconsistencies, particularly regarding vagal maneuvers, were noted. Conclusions: In our cohort, an initial 12 mg adenosine dose was more effective than 6 mg for SVT conversion in the ED. Recognizing and addressing variations in guideline adherence can play a key role in improving patient care. Further prospective research is warranted to optimize dosing strategies and evaluate the impact of standardized protocols on clinical outcomes.